Study on the perception and knowledge of sexual health among adolescents in UiTM Puncak Alam / Nur Hazlizat Hashim - Hashim, Nur Hazlizat (Faculty of Pharmacy, 2010)
Social problems among Malaysian teenagers in the current day are very worrying. Some of the social problems include crime, violence, drug abuse, adultery, rapes, baby dumping and others. However, baby dumping issues are recently become the major concern among publics since the rates of the cases are rapidly increasing. Some argued that this problem arise due to weak knowledge of sexual health among teenagers. Thus, there is an idea proposed by the government to include the sexual education module in the school’s syllabus. Therefore, this research is designed in purpose to gain information on the level of knowledge among adolescents (fresh school leavers) about sexual health. This involves the distribution of questionnaires among fresh school leavers’ students in University Institute Technology MARA (UiTM). Obtained data were analyzed by using SPSS Version 16. An overall observation from the results concluded that, 14.5% of the respondents are not aware of what sexual health really means and do not having enough information about sexual education. Even though the idea of implementation of sexual health education in school has been quite controversial, however it might be the best solution in solving the rapidly increasing social-related problems in the current days.